The development of novel numerical technique for the analysis of the moving vehicle and moving source - Shafrida, Sahrani; Akata, Tatsuya; Kuroda, Michiko (Institute of Electrical and Electronics Engineers Inc, 2015)
The numerical technique for the analysis of the electromagnetic field with moving body or a moving source are required for the effective modeling of new optical devices or microwave devices and also mobile communication field. We have previously proposed the Overset Grid Generation method coupled with FDTD method for the analysis of the EM field with moving boundaries considering Doppler Effect. For higher velocity value, Lorentz transformation is applied to the FDTD method. The time components that were changed in Lorentz transformation are fixed by using linear interpolation scheme in the Overset Grid Generation method. This allows a coherent point in time component with the FDTD method, which is an important element of this proposed numerical technique